Grexit news and stock returns - Andreas Haupenthal; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
During the first eight months of 2015, there was an ongoing debate about whether or not Greece should remain in the euro area. Using an event study approach, we quantify the effects of Grexit-related statements made by six important euro area politicians (Merkel, Schaeuble, Tsipras, Varoufakis, Juncker, and Schulz) on intraday stock returns in Germany, Greece, and the euro area during the period of January 1, 2015 - August 19, 2015. We show that positive statements indicating that a Grexit is less likely lead to higher returns, and negative statements to lower returns. The overall impact of negative statements is more pronounced. The cumulative absolute effects on stock returns are sizeable as the statements contribute to a variation of up to 58 percentage points in the ATHEX. These large effects are of particular relevance as our study only captures an eight month snapshot of the Greek government debt crisis.
Keywords: G01; G12; G14; 330; Event Study; Grexit; Intraday Data; Political Statements; Stock Returns